1983
DOI: 10.1161/01.hyp.5.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-sodium countertransport in erythrocytes of normal and hypertensive subjects. Relationship with age and plasma renin activity.

Abstract: SUMMARY Li,-Na a countertransport was measured in red blood cells of 58 normotensive subjects (27 females and 31 males), 60 patients with essential hypertension (26 females and 34 males), and in 28 with secondary hypertension (19 females and 9 males). The mean values (± SEM) expressed as mmol Li (1 red cells x hr)" 1 were 0.18 ± 0.02 (females) and 0.20 ± 0.01 (males) in the control group, 0.34 ± 0.04 (females) and 0.39 ± 0.03 (males) in essential hypertension, 0.16 ± 0.03 (females) and 0.19 ± 0.02 (males) in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
11
1

Year Published

1984
1984
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 23 publications
(20 reference statements)
8
11
1
Order By: Relevance
“…Correlations of sodium-lithium countertransport with age, 17 measures of body size, 18 and plasma lipid levels 5 have been reported in previous studies. However, because samples for these studies were small or were ascertained through referral clinics or hospitals, the role of these concomitant traits in predicting sodium-lithium countertransport in the general population has remained uncertain.…”
Section: Discussionsupporting
confidence: 67%
“…Correlations of sodium-lithium countertransport with age, 17 measures of body size, 18 and plasma lipid levels 5 have been reported in previous studies. However, because samples for these studies were small or were ascertained through referral clinics or hospitals, the role of these concomitant traits in predicting sodium-lithium countertransport in the general population has remained uncertain.…”
Section: Discussionsupporting
confidence: 67%
“…3). Our finding is at variance with that reported by Winocour et al [14], who showed a correlation, albeit a weak one, between aldosterone and SLC, but is in consonance with that found by Brugnara et al [4].…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, however, subsequent reports have shown a considerable overlap in SLC values between normotensive control subjects and hypertensive patients [4][5][6]. The cause(s) of the implied insufficient specificity of SLC is not clear, but it may be that abnormality of the transport system is present only in a subset of patients with essential hypertension [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Brugnara et al 39 studied normotensive subjects between 10 and 80 years of age, and countertransport correlated inversely with age in their subjects. Burke et al 40 studied 120 normotensive subjects across a similar age range, and they also found a decrease in countertransport with age.…”
Section: -37mentioning
confidence: 98%